Gender-based agency in the PISA global competencies framework - Vegas, Nancy (2021)
Large-scale international assessments such as the Program for International Student Assessments (PISA) have tremendous impact on not just assessing student performance, but also guiding education policy and research. In 2018, PISA adopted a Global Competencies Framework (GCF), shifting its focus from the evaluation of mostly implicit economic citizenship skills to skills connected to a more explicit global citizenship curriculum. In this thesis, I aim to hold PISA accountable to its stated commitments to providing good data about gender equality. I specifically explored the way that PISA produces data about gender-based agency, or the extent to which a student is motivated to act politically on behalf of their gender group. The first research question examined the regimes of knowledge or discourses through which PISA GCF regulated gender subjectivities in their assessment of citizenship competencies. The second research question examined the ways that it measured the gender-based political agency and participation of students. These questions were explored through a Foucauldian discourse analysis and a quantitative content analysis. The findings indicate that the 2018 GCF erased several elements of gender- based identity, agency, and action. Bibliographies and vocabulary can be used in large-scale international assessments to push an intercultural regime of knowledge and restrict gender subjectivities to heteronormative, cisnormative, and universal Western identity. In the case of the 2018 GCF, it resulted in the erasure of indigenous, Black, female and LGBTQ subjectivities, and in colorblind racism. This formulation of global competencies also resulted in the restricted measurement of gender-based political agency, the limitation of student understanding of political participation to interpersonal relations, and the encouragement of students to be neutral rather than to act for social justice.